Emulsion and Foam Templating—Promising Routes to Tailor‐Made Porous Polymers. Issue 32 (25th June 2018) - Stubenrauch, Cosima; Menner, Angelika; Bismarck, Alexander; Drenckhan, Wiebke
Abstract: Emulsions, foams, and foamed emulsions have been used successfully as templates for the synthesis of macroporous polymers. Based on this knowledge this Minireview presents strategies to use, optimise, and upscale these templating methods to synthesise tailor‐made porous polymers. The uniqueness of such polymers lies in the ability to tailor their structures and, therefore, their properties. However, systematic studies on structure–property relations are lacking mainly because the templating scientific community is "split into two": the polydisperse and monodisperse camps. Thus, it is time to build a bridge between the camps, that is, to synthesise porous polymers with very different structures from the same precursors to determine the relationship between the structure and the properties. Abstract : Holey moley : This Minireview presents strategies to use, optimise, and upscale templating methods which use liquid emulsions, foams, and foamed emulsions for the synthesis of macroporous polymers with tailored properties. The importance of bridging work on polydisperse/disordered and monodispsere/ordered porous polymers to advance the understanding of the associated structure/property relations and develop new applications is emphasised.